Examining the relationship between the pre-hospital incident scene management of the paramedic students and their anxiety levels and perception of leadership - Kerkez, Mujde; Ozturk, Mehmet Hayrullah (Elsevier Sci Ltd, 2023)
Aim: The aim of this study is to examine the relationship between the pre-hospital incident scene management of paramedic students and their anxiety levels and perception of leadership. Method: The sample of this descriptive correlational study consisted of 2nd-year students (N = 157) attending the associate degree program of the vocational school of healthcare services in two universities located in the eastern Turkey. No sample selection was used and the study was completed with 130 students. The data were collected using Socio-Demographic Data Form, Incident Scene Description Form, Intolerance of Uncertainty Scale, and Multidimensional Leadership Orientations Scale. The data were analyzed using number, percentage distribution, mean, and standard deviation. Normally distributed data were analyzed by correlation analysis. Results: It was found that 65.4 % of the participants were female, 69.2 % received education on incident scene at the university, 52.3 % stated that this education was adequate, 58.5 % received education on leadership and crisis management at the university, and 60.7 % had no further suggestions for their education at the university. The mean scores of the students' knowledge on incident scene management were 15.77 +/- 4.5, their total mean scores of the Intolerance of Uncertainty Scale were 35.38 +/- 10.31, and their total mean scores of the Multidimensional Leadership Orientations Scale were 57.77 +/- 20.26. A statistically significant negative very weak correlation was found between the Intolerance of Uncertainty Scale and the Multidimensional Leadership Orientations Scale (r = -0.225, p < 0.010). Conclusion: The results of this study revealed that the students had a low level of knowledge about crime scene management. As their anxiety levels increased, their perception of leadership decreased. It can be suggested to organize in-service and simulation trainings that will increase students' awareness of the courses related to crime scene management in their curriculum.
Keywords: Paramedic students; Pre-hospital medical care; Incident scene; Intolerance; Anxiety